Adult Education and Critical Global Citizenship - Makere Stewart-Harawira; Lee Ellis (Adult Education Research Conference, 2007)
This paper addresses two areas of critical concern regarding adult education and conceptions of global citizenship: the impact of deep integration of the Americas and the invisibility of the Indigenous world view in adult education literature regarding citizenship and human rights. It argues for a radial reconceptualization of these key areas.